A Demo of Google Inject - Konstantinou, Loukas; Karapanos, Evangelos (My University, 2026)
We present a demo of Google Inject, a technology-mediated nudge aimed at increasing users’ engagement with fact-checks by injecting fact-checking articles, relevant to one’s query, at the top of Google search results. We elaborate on the problem that Google Inject aims to address, the design and development of the tool, and our ongoing and future empirical work to test its effectiveness in changing individuals’ behaviors.
Keywords: Fact-Checking; Nudging; Online Misinformation